Improvement Quality Health Elderly As Effort Realizing Healthy, Independent, Active and Productive Elderly - Siska Siska; Rifki Wahyudi; Wike Astria; Ahmad Ali Rahmatullah; Yosi Oktarina (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2023)
Elderly or commonly known as elderly is a process of growth and development, so efforts to maintain the health of the elderly are needed so that they are far from various types of diseases. The general condition of the elderly at the Tresna Werdha Budi Luhur Jambi Social Institution seems to be incapable of managing a healthy lifestyle as some of the elderly seem to still smoke in the homestead area, the habit of maintaining personal hygiene which makes the elderly easily affected by diseases such as diabetes mellitus, heart disease, hypertension, ISPA and making another disease. This service activity is held at the Tresna Werdha Budi Luhur Social Institution Jambi from November to December 2022. The aim is for the elderly to understand how to live a clean and healthy lifestyle so that the elderly can regulate their lifestyle and can apply it to their daily lives. A healthy lifestyle can help the elderly maintain or improve their health condition. Efforts to increase PHBS for the elderly must be carried out by motivating the elderly to carry out PHBS and continue to provide counseling about PHBS in orphanages. The total number of participants is 40 seniors. All service program activities run smoothly and are well implemented, with appropriate locations, competent counseling materials, and elders actively participating in these activities.